2016
DOI: 10.1111/den.12657
|View full text |Cite
|
Sign up to set email alerts
|

Reintervention for stent occlusion after bilateral self‐expandable metallic stent placement for malignant hilar biliary obstruction

Abstract: Revisionary SEMS placement is a suitable endoscopic reintervention method for stent occlusion following bilateral SEMS placement from the perspective of time to RBO of the revisionary stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…Risk of reocclusion and patency duration after second stents were similar between plastic and SEMS. 80 In contrast, Inoue et al 81 reported that median time to recurrent biliary obstruction was significantly longer for revisionary SEMS placement than for plastic stents (131 vs 47 days, respectively; log-rank test, P = 0.005). This study investigated hilar obstruction, but a small number of patients was included.…”
Section: Figurementioning
confidence: 94%
“…Risk of reocclusion and patency duration after second stents were similar between plastic and SEMS. 80 In contrast, Inoue et al 81 reported that median time to recurrent biliary obstruction was significantly longer for revisionary SEMS placement than for plastic stents (131 vs 47 days, respectively; log-rank test, P = 0.005). This study investigated hilar obstruction, but a small number of patients was included.…”
Section: Figurementioning
confidence: 94%
“…For each method, the recurrent biliary obstruction (RBO) rate has been reported as 20–55% . Reintervention is required for RBO after SEMS placement, and endoscopic reintervention (ERI) seems to be minimally invasive . However, ERI is sometimes challenging after placement of SEMS, and external drainage tubes may need to be placed after an ERI failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, ERI is sometimes challenging after placement of SEMS, and external drainage tubes may need to be placed after an ERI failure. There is still insufficient evidence to recommend ERI ; therefore, bilateral SEMS placement is sometimes avoided in the management of UMHBO. In our centers, we usually perform SIS placements and have had some patients with RBO after SIS placement .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Inoue et al . reported that the median time to a recurrent biliary obstruction of a revisionary stent is significantly longer for placing a SEMS than that for placing a PS . The Tokyo Criteria use the term ‘recurrent biliary obstruction’ rather ‘patency’ …”
Section: Hilar Obstructionmentioning
confidence: 99%
“…10 In contrast, Inoue et al reported that the median time to a recurrent biliary obstruction of a revisionary stent is significantly longer for placing a SEMS than that for placing a PS. 11 The Tokyo Criteria use the term 'recurrent biliary obstruction' rather 'patency'. 12 CONCLUSION I N CONCLUSION, We described management strategies for acute cholangitis caused by occlusion of both distal and hilar SEMS.…”
Section: Hilar Obstructionmentioning
confidence: 99%